Estrogenic and mutagenic activities of crotalaria pallida measured by recombinant yeast assay and ames test - Boldrin, Paula Karina [UNESP]; Resende, Flávia Aparecida [UNESP]; Höhne, Ana Paula Oliveira [UNESP]; de Camargo, Mariana Santoro [UNESP]; Espanha, Lívia Greghi [UNESP]; Nogueira, Catarine Haidê [UNESP]; Melo, Maria do Socorro F [UNESP]; Vilegas, Wagner [UNESP]; Varanda, Eliana Aparecida [UNESP] (Springer Nature, 2013)
Background: Crotalaria pallida Ailton is a plant belonging to the Fabaceae family, popularly known as rattle or rattlesnake and used in traditional medicine to treat swelling of the joints and as a vermifuge. Previous pharmacological studies have also reported anti-inflammatory, antimicrobial and antifungal activities. Nevertheless, scientific information regarding this species is scarce, and there are no reports related to its possible estrogenic and mutagenic effects. Thus, the purpose of the present study was to investigate the estrogenic potential of C. pallida leaves by means of the Recombinant Yeast Assay (RYA), seeking an alternative for estrogen replacement therapy during menopause; and to reflect on the safe use of natural products to assess the mutagenic activity of the crude extract from C. pallida leaves, the dichloromethane fraction and stigmasterol by means of the Ames test.Methods: The recombinant yeast assay with the strain BY4741 of Saccharomyces cerevisiae, was performed with the ethanolic extract, dichloromethane fraction and stigmasterol isolated from the leaves of C. pallida. Mutagenic activity was evaluated by the Salmonella/microsome assay (Ames test), using the Salmonella typhimurium tester strains TA100, TA98, TA97 and TA102, with (+S9) and without (-S9) metabolization, by the preincubation method.Results: All samples showed estrogenic activity, mainly stigmasterol. The ethanolic extract from C. pallida leaves showed mutagenic activity in the TA98 strain (-S9), whereas dichloromethane fraction and stigmasterol were found devoid of activity.Conclusion: Considering the excellent estrogenic activity performed by stigmasterol in the RYA associated with the absence of mutagenic activity when evaluated by the Ames test, stigmasterol becomes a strong candidate to be used in hormone replacement therapy during menopause. © 2013 Boldrin et al.; licensee BioMed Central Ltd.
Keywords: Ames test; Crotalaria pallida; Estrogenicity; Mutagenicity; Recombinant yeast assay (RYA); dichloromethane; stigmasterol; bacterial metabolism; bacterial strain; controlled study; Crotalaria; drug determination; estrogen activity; estrogen therapy; menopause; mutagenic activity; nonhuman; plant leaf; Saccharomyces cerevisiae; Salmonella typhimurium